2023
DOI: 10.30574/wjarr.2023.17.2.0194
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic evaluation sweet potato (Ipomoea batatas (L) Lam.) genotypes in two agro-ecological zones of Côte d’Ivoire

Abstract: The sweetpotato is the seventh most important crop in the world after wheat, rice, maize, potato, barley and cassava. It is produced annually in all regions of Côte d'Ivoire. Sweetpotato plays a role in food security and income generation for rural populations. However, the crop is facing the challenges of climate change leading to a decline in yields of local cultivars. This phenomenon leads to unproductive soils and the abandonment of many crops, including sweetpotato. To address this problem, 15 sweetpotato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…By implication, these morphological descriptors can be used in diversity studies and characterization of sweet potato varieties in breeding programs. This finding aligns with those of Kouassi et al (2023) but not with the study of Alfred et al (2019), which showed that only 18 of these 21 morphological descriptors were essential in differentiating sweet potato accessions. In Alfred et al (2019) study, the foliage colour of immature leaves and storage root secondary colour intensity were not identified as being essential which is inconsistent with the findings in this study.…”
Section: Discussionsupporting
confidence: 81%
“…By implication, these morphological descriptors can be used in diversity studies and characterization of sweet potato varieties in breeding programs. This finding aligns with those of Kouassi et al (2023) but not with the study of Alfred et al (2019), which showed that only 18 of these 21 morphological descriptors were essential in differentiating sweet potato accessions. In Alfred et al (2019) study, the foliage colour of immature leaves and storage root secondary colour intensity were not identified as being essential which is inconsistent with the findings in this study.…”
Section: Discussionsupporting
confidence: 81%